Cross-National Patterns of Labor Force Withdrawal - Timothy Michael Smeeding; Joseph F. Quinn (Luxembourg Income Study (LIS), 1997)
This paper was originally presented a the Fourth International Research Seminar of the Foundation for International Studies on Social Security (FISS) in June 1997 in Sigtuna, Sweden. In the United States, several public policy initiatives have been undertaken to encourage more work and later retirement among older Americans. Labor force participation data over the past decade suggest that these policies may be working - the early retirement trend seems to have stopped. The purpose of this paper is to analyze retirement patterns in the United States and six other OECD countries to compare their levels and to see if any changes in trends can be discerned over recent years.
Keywords: 330; Altersgrenze; Australien; Deutschland; Großbritannien; Kanada; Niederlande; Schweden; USA